Do foreign banks increase competition? Evidence from emerging Asian and Latin American banking markets - Jeon, Bang Nam; Olivero, María Pía; Wu, Ji (Journal of Banking & Finance, 2011)
In this paper we examine the impact of foreign bank penetration on the competitive structure of domestic banking sectors in host emerging economies. We focus our analysis on Asia and Latin America during the period 1997–2008. Using bank-level panel data to identify foreign banks and to estimate measures of banking competition, we are able to provide robust empirical evidence that an increase in foreign bank penetration enhances competition in these host countries’ banking sectors. We find that this positive foreign bank penetration and banking competition link is associated with a spillover effect from foreign banks to their domestic counterparts. This spillover effect becomes stronger when more efficient and less risky foreign banks enter into less concentrated host country markets. We also find that the spillover effect is greater when foreign banks enter in the form of ‘de novo penetration’ than through mergers or acquisitions of domestic banks (‘M&A penetration’).